2020
DOI: 10.4149/bll_2020_053
|View full text |Cite
|
Sign up to set email alerts
|

LLLT enhance cyclophosphamide induced TRPM2 channel activation in human colon cancer cells

Abstract: AIM: Transient receptor potential (TRP) channels expression is enhanced signifi cantly in colon cancer cells and Low Lever Laser Treatment (LLLT), is known to have effects and is used clinically in the treatment ofmany diseases, including colon cancer. We aimed to reveal the effects of (LLLT) on apoptosis of colon cancer and on the effi cacy of cyclophosphamide via Transient receptor potential melastatin 2 (TRPM2) channels. METHOD: Human colon cancer cells (Caco-2) were cultured and cells were divided into sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…TRPM2 has numerous functions in a variety of cell types and has been shown to be involved in neurological disorders, insulin release, cell motility, and cell death. [6][7][8][9][10] The TRPM2 channel is activated by intracellular adenosine diphosphate ribose, hydrogen peroxide (H 2 O 2 ), intracellular Ca 2+ concentration ([Ca 2+ ] i ), and nicotinic acid adenine dinucleotide phosphate, whereas it is inhibited by the nucleotide adenosine monophosphate and by cellular acidification. [11][12][13][14] Because the TRPM2 channel responds to reactive oxygen species (ROS), it is involved in many oxidative stress-related pathological processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPM2 has numerous functions in a variety of cell types and has been shown to be involved in neurological disorders, insulin release, cell motility, and cell death. [6][7][8][9][10] The TRPM2 channel is activated by intracellular adenosine diphosphate ribose, hydrogen peroxide (H 2 O 2 ), intracellular Ca 2+ concentration ([Ca 2+ ] i ), and nicotinic acid adenine dinucleotide phosphate, whereas it is inhibited by the nucleotide adenosine monophosphate and by cellular acidification. [11][12][13][14] Because the TRPM2 channel responds to reactive oxygen species (ROS), it is involved in many oxidative stress-related pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS might behave as the TRPM2 channel to facilitate cancer therapy. 10,15 Recent studies have shown that 5-fluorouracil (5-FU) and cyclophosphamide may activate the TRPM2 channel in colon or breast cancer cells to enhance cell apoptosis. 15 However, the functional role of the TRPM2 channel in ESCC remains unknown.…”
Section: Introductionmentioning
confidence: 99%